Sub-wavelength waveguide properties of 1D and surface-functionalized SnO2 nanostructures of various morphologies - Bonu, Venkataramana; Sahu, Binaya Kumar; Das, Arindam; Amirthapandian, Sankarakumar; Dhara, Sandip; Barshilia, Harish C. (Beilstein Journal of Nanotechnology, 2019)
One-dimensional (1D) SnO2 sub-wavelength waveguides are a critical contribution to advanced optoelectronics. Further understanding of the surface defects and role of morphology in 1D SnO2 nanowires can help to better utilize these nanostructures more efficiently. For this purpose, three different nanowires (NWs), namely belts, cylindrical- and square-shaped structures were grown using SnO2 quantum dots as a precursor material. The growth process of these NWs is discussed. The nanobelts were observed to grow up to 3 mm in length. Morphological and structural studies of the nanostructures were also carried out. All NWs showed waveguide behavior with visible photoluminescence (PL) upon excitation with a 325 nm laser. This behavior was also demonstrated in tapered and surface-functionalized SnO2 NWs. While the tapered waveguide can allow for easy focusing of light, the simple surface chemistry offers selective light propagation by tuning the luminescence. Defect-related PL in NWs is studied using temperature-dependent measurements and a band diagram is proposed.
Keywords: functionalization; nanowires; photoluminescence; SnO2; sub-wavelength waveguide